2D Motion Graphic Media Through the Applied Behavior Analysis Approach to Stimulate Short Surah Al-Qur'an Reading Ability in Children with Autism - Rahmat Kurniawan; Rina Nurfitri; Amelia Rizky Idhartono (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
The increasing global prevalence of Autism Spectrum Disorder (ASD) necessitates the development of adaptive educational media, particularly to address the core challenges faced by autistic children in verbal communication, maintaining focus, and understanding abstract material, including the religious activity of reading Short Surah of the Qur'an. This gap creates an urgent need for effective teaching tools that are both visually engaging and based on tested behavioral interventions. This research aims to develop an inclusive, child-friendly, and adaptive educational medium to overcome learning saturation and enhance the focus of autistic children in recognizing Al-Qur'an readings. The primary strategy is to integrate the visual-auditory advantages of 2D Motion Graphic Media with the structured behavioral framework of Applied Behavior Analysis (ABA). The media development focuses on Surah Al-Ikhlas, Al-Falaq, and An-Nas. The study adopts a Research and Development (R&D) approach, executed through the phases of Design Thinking (Empathize, Define, Ideate, Prototype, and Testing). The development method includes designing content that applies ABA principles, such as 3-5 times repetition, visual prompting, and consistent reinforcement. The media's visual design is carefully crafted to avoid overstimulation (using high-contrast colors, functional animation, and slow narration). The development subjects are Children with Autism at SLB Tamima Mumtaz. This media is expected to function as an inclusive learning innovation that extends the ABA application model into the context of technology-based religious education.